Подводное сафари: [роман] / Анатолий Сарычев - Сарычев Анатолий Яковлевич (Морской спецназ, 2007)
Экземпляры: Ф. 8 (20250429) / Инвентарный номер: 51042 / Цена: 120.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: С 20 / ББК: 84(2Рос=Рус)6